2019
DOI: 10.1155/2019/5859063
|View full text |Cite
|
Sign up to set email alerts
|

Outer Nuclear Layer as the Main Predictor to Anatomic Response to Half Dose Photodynamic Therapy in Chronic Central Serous Retinopathy

Abstract: Purpose To evaluate the predictors for subretinal fluid resorption in patients with chronic central serous retinopathy (cCSR) submitted to half-dose photodynamic therapy (HD-PDT). Methods Observational, longitudinal, and retrospective study of patients with cCSR submitted to HD-PDT in a tertiary ophthalmology department in Portugal between January 2015 and February 2018. Best-corrected visual acuity (BCVA) and SD-OCT at baseline and 12 ± 3 months after treatment were performed. The central macular thickness (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Foveal ONL thinning is observed not only in various chorioretinal disorders 10 , 28 but also in relatively benign conditions such as drusen or pachychoroid pigment epitheliopathy 9 , 11 , indicating that ONL may correspond very sensitively to photoreceptor vitality. Thick ONL is considered a predictor for SRF resorption in chronic central serous chorioretinopathy treated with photodynamic therapy 29 . In this study, nAMD eyes also showed more ONL thinning and decreased visual acuity on baseline testing compared to the control eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Foveal ONL thinning is observed not only in various chorioretinal disorders 10 , 28 but also in relatively benign conditions such as drusen or pachychoroid pigment epitheliopathy 9 , 11 , indicating that ONL may correspond very sensitively to photoreceptor vitality. Thick ONL is considered a predictor for SRF resorption in chronic central serous chorioretinopathy treated with photodynamic therapy 29 . In this study, nAMD eyes also showed more ONL thinning and decreased visual acuity on baseline testing compared to the control eyes.…”
Section: Discussionmentioning
confidence: 99%
“…However, anatomic response was not correlated with time until treatment as observed previously. 3,16,18 Most studies used a 577 nm or 810 nm wavelength and a 10-15% duty cycle. Five percent duty cycle were used by the PACORES group 14 and Malik et al 10 The PACORES group presented 92 eyes treated with 577 nm SML and a 12-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A resorption of ≥50% of SRF was considered a positive anatomical response. 16 All statistical analysis was performed using SPSS software version 25.0 (SPSS Inc., Chicago, IL) and p values <0.05 were considered statistically significant. Nonparametric tests were applied after non-normality of the sample was confirmed by Shapiro-Wilk test.…”
Section: Methodsmentioning
confidence: 99%